The Phenomena of Kabalutan In The Highlights of Islamic Marriage Law - Nokoe, Nurhayati Sutan; Susilawati, Susi; Yunus, Nursiah Moh; Ridwan, Ashar; Nurman, Ilham (Batulis Civil Law Review, 2023)
Introduction: The ease of carrying out marriages and divorces in Kabalutan Village, Talatako District, Tojo Una Una Regency. One of the local residents was reported by the mass media that for marriage or divorce it is enough to bring it to the Penghulu. Whereas the real task of the Penghulu is to provide supervision and registration of marriages. Can get married if the bride does not have a Guardian.Purposes of the Research: It is important to know and analyze how the implementation of marriage in Kabalutan Village is viewed from the perspective of Islamic law.Methods of the Research: The method used is an empirical legal research method with primary data sources from religious leaders, community leaders, and the community in the village.Results of the Research: So that the validity of a marriage is realized and in accordance with the objectives of the Marriage Law and also the Compilation of Islamic Law which states that marriage is a marriage, namely a very strong contract or mitsaqan ghalizhan to obey Allah's commands and carry them out is worship. The people of Kabalutan Village generally have unregistered marriages or marriages that are not registered due to the long distance and the cost of accommodation which is quite expensive to report and register their marriages to the relevant agencies.